(untitled) (Architecture Image Studies, 2025)
Modern architecture has witnessed radical transformation with emergence of the concept of a smart building, which relay on internet of Things (IOT) technologies to improve the environmental and operational Energy Performance this study aims to explore the impact of interactive architectural design using (IOT) technologies on the development of a smart building in Iraq’s hot and dry climate by comparing global and local architectural models. The papers examine five principal case studies- World smart projects and local project covering heritage designs and simi- smart models focusing on green. performance indicators, energetic performance, and climate navigation. The result demonstrated the advantages of interactive smart projects in decreasing internal heat load and energy consumption by as much as 50 percent below conventional buildings. The work also revealed a potential for and local buildings (the Sunni endowment building in the International City Stadiums, towards wise and interactive through consideration of local potentials. and conditions.